2004
DOI: 10.1016/s0006-3495(04)74166-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Supported Intermembrane Junctions

Abstract: Supported intermembrane junctions, formed by rupture of giant unilamellar vesicles onto conventional supported lipid membranes, have recently emerged as model systems for the study of biochemical processes at membrane interfaces. Using intermembrane fluorescence resonance energy transfer and optical standing wave fluorescence interferometry, we characterize the nanometer-scale topography of supported intermembrane junctions and find two distinct association states. In one state, the two membranes adhere in clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
133
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 49 publications
8
133
1
2
Order By: Relevance
“…Supported lipid bilayer (SLB), an artificial mimic of the natural cell membrane, which is compatible with protein incorporation and possesses sustained lateral mobility, [20][21][22][23][24][25][26] has been studied extensively as model system of biological membranes over past decades. Previously, many studies have demonstrated that this biomimetic multifunctional material has great bioinert property and lateral mobility, thus leading to effective resistance of non-specific proteins adsorption and cells adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Supported lipid bilayer (SLB), an artificial mimic of the natural cell membrane, which is compatible with protein incorporation and possesses sustained lateral mobility, [20][21][22][23][24][25][26] has been studied extensively as model system of biological membranes over past decades. Previously, many studies have demonstrated that this biomimetic multifunctional material has great bioinert property and lateral mobility, thus leading to effective resistance of non-specific proteins adsorption and cells adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid bilayers can be readily interfaced with solid substrates while retaining their natural 2D fluidity (11)(12)(13); half of our junction consists of such a supported bilayer, assembled on SiO 2 . A single species of protein (an IgG antibody) is bound to the supported bilayer, and a ruptured giant lipid vesicle (14,15) provides the second lipid bilayer half of the intermembrane junction. The quasi-planar geometry allows us to image the intermembrane topography via several concurrent, complementary techniques: direct fluorescence microscopy, intermembrane fluorescence resonance energy transfer (FRET) microscopy (16)(17)(18)(19), and fluorescence interference contrast (FLIC) microscopy (14-18, 20, 21).…”
mentioning
confidence: 99%
“…To allow any radial deformations of the impermeable bilayer, there must be some area change of the surface. One may imagine that the surface of a tensed GUV is essentially inextensible, however, even such tensed structures contain a reservoir of extra area hidden in the (small-scale) thermal undulations of the surface [13,40]. Thus the two-dimensional bulk modulus of the viscous shell is dominated by a large, but finite elastic component.…”
Section: B a Viscous Shellmentioning
confidence: 99%